Thinking Frantz Fanon for a new pedagogy from blackness, humanism and praxis of liberation - Pizarro, M (2018)
In this text we seek to analyze the proposals of the thought of Frantz Fanon in The Damned of the Earth in order to trace the pedagogical proposals that are implicit throughout his opus magnum. We believe that in the ideas that Fanon discusses in a political way we would find certain pedagogical traits with which we want to dialogue. For these purposes, we divide the present writing into three parts. 1) At first, we give an overview of the thinking of Frantz Fanon, his works and influences in the liberation movements. 2) Taking one more step, then, we make a study of the works of Frantz Fanon already mentioned, in order to trace the proposals of blackness and pedagogy as praxis of liberation, in addition to the idea of people as subject of this same praxis and not as a passive block. 3) Finally, we analyze the reading of colonial thinking represented by Catherine Walsh. In such a way that we round up the first two notions: the ideas of blackness and the pedagogical traces worked in the previous part. In the end, then, we hold the importance of the two ideas worked in the thought of the thinker of Martinique.